VD_FINDINFO HC / 2020 / 729 vom 29. Oktober 2018 - VD Tribunal cantonal (2018)
CONTRAT DE TRAVAIL, RÉSILIATION ABUSIVE, INDEMNITÉEN GÉNÉRAL | 328 al. 1 CO, 336 al. 1 let. a CO, 336 al. 1 let. d CO, 336a al. 1 CO, 336a al. 2 CO